Shields for Emotional Well-Being in Chinese Adolescents Who Switch Schools: The Role of Teacher Autonomy Support and Grit - Lan, Xiaoyu; Zhang, Lifan (Frontiers in Psychology, 2019)
Although prior research has demonstrated that switching schools poses a risk for academic and behavioral functioning among adolescents, relatively little is known about their emotional adjustment, or how it affects emotional well-being. Moreover, the cumulative effects of multiple risk and protective factors on their emotional well-being are even less covered in the existing literature. Guided by a risk and resilience ecological framework, the current study compared emotional well-being, operationalized as positive affect and negative affect, between adolescents who had switched schools and their non-switch counterparts, and examined the direct and interactive effects of teacher autonomy support and two facets of grit (i.e., perseverance and consistency) on emotional well-being in both groups. A propensity score matching analysis was used to balance the two groups in terms of sociodemographic characteristics (i.e., age, gender, and socioeconomic status). A total of 371 adolescents who had switched schools and 742 non-switch counterparts aged from 13 to 18 years were involved in this study. Results indicated that adolescents who had switched schools reported higher levels of negative affect than their non-switch counterparts. Moreover, for adolescents who had switched schools, those who possessed higher levels of perseverance had a significantly negative association between teacher autonomy support and negative affect; however, the corresponding association was independent of perseverance for their non-switch counterparts. The current findings indicate that switching schools is a disadvantage for adolescents’ emotional states. However, teacher autonomy support and perseverance can protect adolescents who switch schools as critical stress-buffering factors against these negative feelings.